Are you a panic buyer? Observations from consumers in Malaysia / Yee-Cheak Chan, Yen-Nee Goh and Chee-Ngee Lim - Chan, Yee-Cheak; Goh, Yen-Nee; Lim, Chee-Ngee (Universiti Teknologi Mara, Selangor: Puncak Alam Campus: Faculty of Business and Management, 2023)
Panic buying is an intriguing social phenomenon during a crisis. However, the existing literature primarily emphasises impulsive purchases and fails to address the objective of panic buying. A minimal study has examined panic buying, integrating variables within an S-O-R framework throughout a crisis. Therefore, this study bridges the existing gaps by examining the variables influencing panic buying behaviour in Malaysia. The quantitative and purposive sampling techniques were used to evaluate Malaysians aged 18 and above who have previously encountered panic buying. A total of 280 questionnaires were collected via distribution to social media platforms. Findings reveal that information overload impacts cyberchondria and perceived severity. Furthermore, price consciousness affects panic buying behaviour. No link is found between perceived severity and cyberchondria towards panic buying behavior. This study theoretically contributes to the literature on the variables influencing panic buying behaviour in Malaysia. This study enhances consumers' decision-making knowledge during a crisis. This study also provides insights to the government in ensuring product stability and business operators to undertake appropriate strategies pre- and post-crisis. Future research should consider the developed countries and different product categories.